A VOLUME INTEGRAL CODE FOR EDDY-CURRENT NONDESTRUCTIVE EVALUATION - Sabbagh, Harold A. (Applied Computational Electromagnetics Society Journal (ACES), 2022)
This paper is an extension of J. R. Bowler, H. A. Sabbagh, and L. D. Sabbagh, "A Computational Model of Eddy-Current Probes Over a Stratified Composite Workpiece," which was presented at the 4th Annual Review of Progress in Applied Computational Electromagnetics, Monterey, CA, March 1988. It describes an application of modern methods of computational electromagnetics to the problem of eddy-current nondestructive evaluation (NDE). Specifically, a volume integral equation is developed that can be used to model eddy-current probes with ferrite cores, or it can be used to compute flaw-field interactions. Both of these problems are of considerable importance in applying electromagnetic techniques to NDE, for they are intimately involved in detecting flaws, and inverting eddy-current data for reconstructing flaws. The model is fully three-dimensional, and the discretized integral equation is solved iteratively using conjugate gradients and FFT techniques. Problems with 12,000 unknowns are being routinely solved on the Alliant FX/ 1 minisupercomputer in reasonable times. The model is used to compute such important probe parameters as impedance and coupling. It is also used to compute the electromagnetic response of flaws as the geometry of the flaw changes, or as a function of frequency. [Vol. 4, No. 1, pp.3-22 (1989)]